NGAL As A Biomarker For Early Detection Of Renal Allograft Dysfunction In Living Donor Transplantation - Norkuziev, Sherali Safaralievich; Kurbanov Obid Makhsudovich; Muminov Javokhir Asliddinovich; Ismatov Tuichiboy Akhrorkulovich; Norkabilov Alisher Norbekovich; Olimov Ismoilkhon Zhamolkhon ugli; Mamatmurodov Anvar Abdusaidovich (Zien Journals, 2025)
This open-label, randomized, retrospective, comparative study investigated the prognostic value of urinary NGAL (neutrophil gelatinase-associated lipocalin) levels in predicting renal allograft dysfunction in 18 patients who underwent living related donor kidney transplantation at the Samarkand Regional Multidisciplinary Medical Center between January and September 2024. Participants were followed up for three months after transplantation. Renal graft dysfunction (DGF) was defined based on the criteria of Halloran et al. Dynamic measurements of NGAL, serum creatinine, and urea during the first week of the postoperative period showed a significant decrease in these parameters in 17 of 18 patients. Graft dysfunction was observed in one case, which was accompanied by abnormalities. The data obtained confirm that NGAL is a useful biomarker for the early diagnosis and monitoring of renal graft function. This method may improve the prediction of complications and optimize the clinical management of patients after kidney transplantation.
Keywords: NGAL; kidney transplantation; graft dysfunction